Analysing Gender and Temporal Dynamics in Human Mobility Patterns in Central Sweden - Paria Sadeghian; Brian Babak Mojarrad (Geographies)
Human mobility plays a fundamental role in urban life, shaping the development of infrastructure, transportation systems, and public spaces. Understanding the dynamics of mobility patterns is essential for creating sustainable and inclusive urban environments. This study investigates the influence of gender and temporal variations on human mobility within a city in central Sweden, shedding light on how movement patterns fluctuate throughout the day and differ across gender groups. The findings reveal significant temporal shifts in mobility hotspots, with individuals travelling to different areas at varying intensities depending on the time of day. These variations highlight the dynamic nature of urban movement and emphasise the necessity of time-sensitive urban planning strategies. While overall journey patterns between genders exhibit relatively small differences, a closer analysis uncovers distinct gender-based disparities in mobility hotspots, indicating that men and women tend to frequent different locations with varying travel behaviours. These insights provide valuable input for urban planners, policymakers, and transportation authorities seeking to enhance accessibility, safety, and efficiency in urban mobility networks. Recognising the interplay between gender and temporal mobility patterns can lead to more equitable infrastructure design, ensuring that urban spaces accommodate diverse mobility needs. By emphasising the importance of these factors, this study contributes to a broader understanding of human mobility behaviour and underscores the need for data-driven planning approaches that address spatial and temporal variations in movement patterns.